Alpha: From the International Style to the International Space Station. (November 2014) - Adams, Constance; Jones, Rod
<x xml:space="preserve">Abstract</x> How has a Modernist predilection for the modular contributed to the design of Space Architecture? Leading space architects ConstanceAdams and Rod Jones highlight how by embracing a diligent modularity in the early 1980s, NASA initiated a design approach that has enabled replicability, flexibility and technological transparency, and has proved the International Space Station resilient in the face of multiple logistical, financial and political challenges.